Kekuatan Awal Stabilisasi Gambut Menggunakan Geopolimer Dengan Variasi Molaritas NaOH - Septari, Dinda; Wibisono, Gunawan; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2022)
Subgrade is very important in road construction. Peat have high organic matter with low bearing capacity, need to be stabilized before being used as a subgrade. Geopolymer’s made by mixing fly ash with alkali activator and regarded as an eco-friendly materials for soil stabilization and suitable for peat soil because its ability to resist in acid organic environment. In this research, NaOH and Na2SiO3 was selected as alkali activator. Using cement as additive in geopolymer can accelerate hardening process in room temperature. This research aims to find the optimum composition of the geopolymer hybrid for peat stabilization using the UCS (Unconfined Compressive Strength) test by varying the NaOH molarity. Variations of NaOH used in this research were 8M, 10M, and 12M with Na2SiO3/NaOH ratio of 1,5/1 and curing period of 7 and 14 days. Result of this research show that the highest compressive strength value is found in the variation of NaOH 8M aged 7 days with compressive strength of 24,24 kPa.Keywords: Peat, Stabilization, Geopolymer Hybrid, NaOH Molarity, UCS